Robotic Surgery in Rectal Cancer - Oliveira, Sara Margarida Leonardo de; Barbosa, Laura Elisabete Ribeiro (Journal of Coloproctology, 2021)
Rectal cancer is an important cause of morbidity and mortality worldwide. The most effective and curative treatment is surgery, and the standard procedure is total mesorectal excision, initially performed by open surgery and posteriorly by minimally invasive techniques. Robotic surgery is an emerging technology that is expected to overcome the limitations of the laparoscopic approach. It has several advantages, including a stable camera platform with high definition three-dimensional image, flexible instruments with seven degrees of freedom, a third arm for fixed retraction, fine motion scaling, excellent dexterity, ambidextrous capability, elimination of physiological tremors and better ergonomics, that facilitate a steady and precise tissue dissection. The main technical disadvantages are the loss of tactile sensation and tensile feedback and the complex installation process. The aim of the present study is to review the importance and benefits of robotic surgery in rectal cancer, particularly in comparison with the laparoscopic approach. Intraoperative estimated blood loss, short and long-term outcomes as well as pathological outcomes were similar between robotic and laparoscopic surgery. The operative time is usually longer in robotic surgery and the high costs are still its major drawback. Robotic surgery for rectal cancer demonstrated lower conversion rate to open surgery and benefits in urinary and sexual functions and has been established as a safe and feasible technique.
Keywords: rectal cancer; minimally invasive surgery; robotic surgery